Modern trends in technical support of agricultural producers - Asadullin Nail (EDP Sciences, 2021)
In modern conditions of the development of an innovative economy, the scientific literature does not reveal the main problems of strengthening the material and technical base of agricultural producers. The agricultural machinery market is practically absent, the issue of formation and functioning remains unresolved. The article is devoted to the assessment of the current state of the provision of agricultural commodity producers with equipment, the development of the tractor and agricultural machine-building industry in Russia, the disclosure of problems, and the search for solutions to the problem of complex mechanization of agriculture in modern conditions. The scientific novelty of the work is determined by the substantiation of the need to solve the problems of strengthening the material and technical base of the subjects of agricultural business and the proposed practical recommendations for the development of the innovative basis of agriculture. The article reveals the main trends in the change in the output of elements of the material and technical base of agriculture, reveals the problems that restrain the process of technical renewal of agricultural production, suggests ways to increase the provision of technical means for the innovative development of the agrarian sector of the economy. The theoretical and practical results of the study can be recommended for use in the formation of programs for the development of technical equipment in the agricultural sector, planning of agricultural production, economic analysis of the economic activities of agricultural enterprises and organizations.